Terahertz Photonic Crystal Fiber Sensor for Cancer Cell Detection: Performance Analysis and Discrimination - Kayab Khandakar; Md. Omar Faruk; A. H. M. Iftekharul Ferdous; Md. Naimur Rahman Naim (Cancer Medicine)
ABSTRACT Background Cancer cells exhibit significant heterogeneity, making their detection a challenging task. Methods In this study, a unique Photonic Crystal Fiber (PCF) sensor with a circular core design and curved trapezoidal cladding is presented. It is especially designed to detect cancer cells efficiently. Results The proposed sensor demonstrates exceptional performance, achieving a maximum relative sensitivity (RS) of 99.71% for breast cancer type II cells, along with similarly high sensitivities for cervical, adrenal gland, skin, blood, and breast cancer type I cells. Key performance parameters highlight its accuracy in detecting cancer cells via minute changes in refractive index (RI), including ultra‐low confinement loss (CL) of up to 6.69 × 10−13 dB/cm and effective material loss (EML) as low as 0.00161 cm−1. Conclusions The sensor's high accuracy, rapid response time, and ability to selectively target tumor cells make it a breakthrough in early cancer detection. Moreover, its compact size and potential for easy fabrication enhance its applicability in emergency settings. This cutting‐edge approach represents a major advancement in medical technology, paving the way for more efficient and targeted cancer diagnostics.